2021
DOI: 10.3390/cells10010163
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Role of Heme Oxygenase-1 in Angiotensin II-Induced Abdominal Aortic Aneurysm in the Normolipidemic Mice

Abstract: Abdominal aortic aneurysm (AAA) bears a high risk of rupture and sudden death of the patient. The pathogenic mechanisms of AAA remain elusive, and surgical intervention represents the only treatment option. Heme oxygenase-1 (HO-1), a heme degrading enzyme, is induced in AAA, both in mice and humans. HO-1 was reported to mitigate AAA development in an angiotensin II (AngII)-induced model of AAA in hyperlipidemic ApoE-/- mice. Since the role of hyperlipidaemia in the pathogenesis of AAA remains controversial, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Furthermore, HMOX1 can downregulate MMP-12 expression [ 54 ], and although not directly attributable to MMP-12, HMOX1 deficiency aggravated AAA development in Ang II-infused Apoe −/− mice [ 55 ]. However, HMOX1 deficiency appears protective in normocholesterolemic mice, limiting AAA formation [ 56 ], similar to the proposed dual actions of MMP-12 [ 29 ].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, HMOX1 can downregulate MMP-12 expression [ 54 ], and although not directly attributable to MMP-12, HMOX1 deficiency aggravated AAA development in Ang II-infused Apoe −/− mice [ 55 ]. However, HMOX1 deficiency appears protective in normocholesterolemic mice, limiting AAA formation [ 56 ], similar to the proposed dual actions of MMP-12 [ 29 ].…”
Section: Discussionmentioning
confidence: 91%
“…Increased age is a significant risk factor for the development of AAA in humans 38 . Similarly, the incidence of AAA following AngII infusion has been shown to be increased in aged (18–20 months) nonhyperlipidemic C57 wild-type mice, as compared to younger mice (2–3 months).…”
Section: Resultsmentioning
confidence: 99%
“…HO-1 has been reported to attenuate the development of AA in mouse models induced by Ang-II. However, Kopacz et al revealed the dual role of HO-1 in AA formation, which can prevent the development of AA while simultaneously exacerbating the formation of AA states and reducing the risk of rupture [ 100 , 101 ].…”
Section: Oxidative Stress In Common Vascular Diseasesmentioning
confidence: 99%